Poverty and Nutrition in Bolivia - World Bank (Washington, DC, 2013)
Malnutrition is crippling Bolivia, and the country must now face the political, and bureaucratic failure in addressing malnutrition. This study defines the nature, and extent of the malnutrition problem in the country, identifies the underlying reasons for the failed response, and outlines actions for both immediate, and more long-term results. The study further estimates that less than ten percent of government, and non-government expenditures, with an explicit nutrition, or food security component, is devoted to effective programs serving the neediest - poor pregnant women, and malnourished children under two. Public and private expenditures on nutrition are often misdirected, for although Bolivia did achieve successes in the advancement of nutrition over the past twenty years, the problem of malnutrition still requires action on several fronts. Primarily, nutrition needs a national strategy, and functional leadership, able to provide the population with accurate, and practical nutritional knowledge, prioritizing effective interventions for the most vulnerable. The study suggests improvements in program design, by targeting assistance, and exploiting the opportunities to improve nutrition through water and sanitation, rural development, roads, and education projects, which can have a profound effect on nutrition. Recommendations include the development of nutrition education focused on high-priority population, towards creating a private commission to demand continuity of Government attention to nutrition, as well as community participation in nutrition programming.